(P039) Dose-Dependent Change in T2 Relaxation Time Constant in Sarcoma and Normal Tissue. - Chenyang Wang; Yingli Yang; Minsong Cao; Low, Daniel; Kamrava, Mitchell (Oncology (08909091))
INTRODUCTION: Magnetic resonance imaging (MRI) T2 relaxation time constant mapping is a technique that characterizes T2 relaxation curve via exponential fitting of T2-weighted MR images at different echo times, and the resulting relaxation time constant has been shown to correlate with macromolecular property of physiological tissue. METHODS: The MRI plan was approved by the institutional review board at our institution. MRI was carried out on a 0.35T whole body MRI scanner before and after preoperative radiation to retroperitoneal sarcoma for 28 Gy in eight fractions. Pulse sequence consists of a turbo spin echo (TSE) sequence with TR of 2,000 ms, TE = [28, 56, 98, 140] ms, matrix = 256 × 256 × 10, slice thickness = 1.5 mm, average = 4, and turbo factor = 10. A T2 relaxation time constant map was generated by applying voxel-by-voxel exponential fitting for images acquired at each TE. Regions of interest, including tumor, iliac bone, and iliacus muscles, were drawn on T2-weighted images and applied to the T2 relaxation time constant map to extract mean T2 relaxation time constant values for each structure. RESULTS: Retroperitoneal sarcoma demonstrated a significant increase in mean T2 relaxation time constant after 28 Gy, with a mean increase of 14.02% (P < .05). Ipsilateral iliac bone adjacent to the sarcoma showed a decrease in T2 of 20.33%, while the contralateral side showed a minimal change of 1.71% (P < .0005). DISCUSSION: Our results demonstrate that there is a measurable T2 relaxation time constant change in retroperitoneal sarcoma after 28 Gy. In addition, normal tissue, such as the iliac bone, appears to demonstrate a significant dose-dependent change in T2, since only the ipsilateral iliac bone near the radiation field exhibited significant change. Our results indicate that T2 measurement has the potential to characterize tumor and normal tissue responses to radiation.